Pre-service english teachers’ perceptions of language assessment in a colombian language teacher education program - Sonia Patricia Hernández-Ocampo; Pedro Antonio Chala-Bejarano; Magda Rodríguez-Uribe (International Journal of Educational Research Open)
This phenomenological study explored the perceptions of pre-service English teachers about language assessment in a private university in Colombia. Using a survey and a focus group, data were collected from 179 participants. Results show that many pre-service teachers limit their view of assessment merely to testing and tend to criticize teachers’ subjectivity, understood as the teacher's judgement on the basis of their opinion rather than stated criteria, and the adverse feelings caused by testing (e.g. frustration, anxiety and fear). Other participants see assessment as an integrative practice and highlight the benefits for their learning process, mainly as a result of feedback. For these pre-service teachers, feedback allows them to understand the topics and helps them to identify their weaknesses. Implications discuss the importance of leading processes of reflection and awareness about assessment as well as about the purposes and forms of feedback given to students, essential topics in the knowledge base of English language teachers. This could be achieved through in-class discussions that help students to understand what is assessed together with how and why they are assessed; in this way, they can reflect on their own learning process and later be able to assess their future students soundly.